Methodology of Global Adult Tobacco Survey (GATS), Malaysia, 2011. - Azahadi Omar,; Muhammad Fadhli Mohd Yusoff,; Tee, Guat Hiong; Tahir Aris,; Jeremy, Morton; Sameer Pujari, (Universiti Kebangsaan Malaysia, 2013)
Malaysia participated in the second phase of the Global Adult Tobacco Survey (GATS) in 2011. GATS, a new component of the Global Tobacco Surveillance System, is a nationally representative household survey of adults 15 years old or above. The objectives of GATS Malaysia were to (i) systematically monitor tobacco use among adults and track key indicators of tobacco control and (ii) track the implementation of some of the Framework Convention of Tobacco Control (FCTC)-recommended demand related policies.